1980
DOI: 10.1007/bf01886622
|View full text |Cite
|
Sign up to set email alerts
|

The visual sensitivity of women during the menstrual cycle

Abstract: Five women were examined with dark adaptometry and a signal detection procedure for seven consecutive days in the middle of their menstrual cycles. Their discriminability indices show significant (p < 0.05) increases in visual sensitivity on the basal body temperature rise day, while five control observers show no changes across four consecutive days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
(11 reference statements)
1
16
1
Order By: Relevance
“…Scher, Pionk, and Purcell (1981) demonstrated that dark-adapted visual sensitivity (d~) was increased at ovulation but was unchanged at other phases of the menstrual cycle. This finding was consistent with earlier work that had also found dark-adapted sensitivity to be increased at or around the time of ovulation (Barris, Dawson, & Theiss, 1980;Ward, Stone, & Sandman, 1978). In addition, Scher et al (1981) found no effect of cycle phase under light-adapted conditions.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Scher, Pionk, and Purcell (1981) demonstrated that dark-adapted visual sensitivity (d~) was increased at ovulation but was unchanged at other phases of the menstrual cycle. This finding was consistent with earlier work that had also found dark-adapted sensitivity to be increased at or around the time of ovulation (Barris, Dawson, & Theiss, 1980;Ward, Stone, & Sandman, 1978). In addition, Scher et al (1981) found no effect of cycle phase under light-adapted conditions.…”
supporting
confidence: 92%
“…Experimental data were collected on the 1 st day of menses and on the day of the rise in a subject's basal body temperature. This would be the day after ovulation and was the day on which Barris et al (1980) had found the greatest increase in visual sensitivity. To ensure accuracy of phase of testing, the basal body temperature was monitored throughout the menstrual cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators demonstrated changes in some visual functions that suggested better visual performance during ovulation [2,3,4,5,6]. However, no detailed study was performed to assess colour vision.…”
Section: Introductionmentioning
confidence: 99%
“…Visual thresholds tend to be lowest at the time of ovulation (e.g., Barris, Dawson, Theiss, 1980, andScher, Pionk, &Purcell, 1981). Olfactory thresholds also tend to be lower at midcycle than during menstruation (e.g., Mair, Bouffard, Engen, & Morton, 1978).…”
mentioning
confidence: 99%